KELEKATAN KERJA, KETERIKATAN KERJA, DAN NIAT UNTUK PINDAH KERJA (Studi Kasus Pada Dosen Universitas Muhammadiyah Cirebon) - Asep Gunawan; Robiah Azzahra (Prodi Ilmu Manajemen, Fakultas Ekonomi Universitas Muhammadiyah Cirebon, 2017)
The purpose of this study was to determine the influence of job embeddedness and work engagement together towards turnover intention at University lecturer Muhammdiyah of Cirebon. With the product moment correlation techniques of Karl Pearson and Cronbach Alpha technique, the data of this study are eligible valid and reliable. Test the hypothesis using multiple linear regression techniques, with the dependent variable of turnover intention as well as the independent variable is job embeddedness and turnover intention. The population in this research is University lecturer Muhammadiyah Cirebon, the sampel in this study amounted to 51 respondents. Methods of data collection in this study is a quantitative manner of data collection methods using quesionnaires. The results indicate that Job Embeddedness (X1) has no effect on Turnover Intention (Y), it is shown from the results that the for Job embeddedness variable (X1) of -1.327 is smaller than (-1.327 <1.680), Work Engagement (X2) is not have an influence on Turnover Intention (Y), it is shown from the results seen that for variable Work Engagement (X2) of 0.141 is smaller than (0.141 <1.680), Job embeddedness (X1) and Work Engagement (X2) does not affect Turnover Intention (Y) with the results of the testing showed that the test F of 0.904. Thus < (0.904 <2.790). Keywords : Job Embeddedness, Work Engagement, and Turnover Intention